Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Impacts of land use change on carbon storage in termite mounds of South Africa - Teneille Nel; Catherine E. Clarke; Michele L. Francis; Brian Sakala; Daniel O. Breecker; Timothy Gallagher; Carlos A. Sierra (CATENA, 2025)

Carbon dynamics in termite mounds: The effect of land use on microbial oxalotrophy - Teneille Nel; Catherine E. Clarke; Michele L. Francis; Darya Babenko; Alf Botha; Daniel O. Breecker; Don A Cowan; Timothy Gallagher; Pedro Lebre; Joseph R. McAuliffe; Alyssa N. Reinhardt; Marla Trindade (CATENA, 2025)

First records of the roughskin dogfish Centroscymnus owstonii in the greater Antilles, central Caribbean Sea, Western Atlantic Ocean - Olivia F. L. Dixon; Shannon E. Aldridge; Johanna K. Kohler; Anne Veeder; Paul Chin; Teresa F. Fernandes; Timothy Austin; Rupert F. Ormond; Mauvis A. Gore; Diego F. B. Vaz; Austin J. Gallagher (Journal of Fish Biology, 2025)
The roughskin dogfish Centroscymnus owstonii , a deep‐sea shark, has a patchy global distribution, with most knowledge stemming from incidentally captured specimens. Using a deep‐sea remote lander video system, we observed multiple C. owstonii individuals alive on the footage at 1054 m off Little Cayman, Cayman Islands, Western Atlantic Ocean, marking, to our knowledge, the first record of the species in the Greater Antilles, central Caribbean Sea, while also adding a new species locality record for the Cayman Islands. This study expands our knowledge of the distribution of the roughskin dogfish in the region, and highlights the utility of video lander systems for enhancing and expanding our understanding of the biology and diversity of deep‐sea sharks.

Integrating high-resolution imagery, deep learning, and GIS to estimate soil erosion following timber harvesting - Manisha Parajuli; Richard Cristan; Marissa Jo Daniel; Arjun Rijal; Dana Mitchell; Timothy McDonald; Tom Gallagher (Remote Sensing Applications: Society and Environment, 2025)

Corrigendum: Renewed occurrence of schooling scalloped hammerhead (Sphyrna lewini) and of great hammerhead (S. mokarran) sharks in the Cayman Islands - Mauvis Gore; Johanna Kohler; Rupert Ormond; Austin Gallagher; Teresa Fernandes; Timothy Austin; Christy Pattengill-Semmens (Frontiers in Marine Science, 2024)

PFAS remediation: Evaluating the infrared spectra of complex gaseous mixtures to determine the efficacy of thermal decomposition of PFAS - Kendall D. Hughey; Neal B. Gallagher; Yuwei Zhao; Nikita Thakur; Ashley M. Bradley; Paul G. Koster van Groos; Timothy J. Johnson (Chemosphere, 2024)

Postharvest evaluations of soil erosion, ground cover, and best management practice implementation on integrated biomass and conventional clearcut harvest sites - Manisha Parajuli; Tom Gallagher; Richard Cristan; Marissa Jo Daniel; Dana Mitchell; Timothy McDonald; Arjun Rijal; Jingyi Zheng (Forest Ecology and Management, 2024)

Depth Range Extension for the Misty Grouper Hyporthodus mystacinus Documented via Deep-Sea Landers throughout the Greater Caribbean - Shannon E. Aldridge; Olivia F. L. Dixon; Christine de Silva; Johanna K. Kohler; Oliver N. Shipley; Brennan T. Phillips; Teresa F. Fernandes; Timothy Austin; Rupert F. Ormond; Mauvis A. Gore; Austin J. Gallagher (Fishes, 2024)
Misty Groupers (Hyporthodus mystacinus) are one of the largest and most geographically widespread grouper species and one of the few grouper species known to occur at depths greater than 200 m. However, aspects of their basic biology, behavior, and ecology remain poorly understood, leaving significant gaps in our ability to evaluate their functional role throughout the vertical water column, as well as our understanding of their conservation needs in a changing ocean. Through in-situ video observation obtained using deep-sea landers in both The Bahamas and Cayman Islands over multiple years, we documented Misty Grouper occurrence up to 470 m depth in the mesopelagic zone. These observations provide a new depth range extension for the species and illuminate the potential importance of deep-water habitats for large grouper species in the wider Caribbean.

Renewed occurrence of schooling scalloped hammerhead (Sphyrna lewini) and of great hammerhead (S. mokarran) sharks in the Cayman Islands - Mauvis Gore; Johanna Kohler; Rupert Ormond; Austin Gallagher; Teresa Fernandes; Timothy Austin; Christy Pattengill-Semmens (Frontiers in Marine Science, 2024)
The scalloped hammerhead shark (Sphyrna lewini) , a critically endangered species with a decreasing global population, is characterised by its occurrence in large schools. Such schools are still observed today in the Pacific Ocean, but this is generally not the case in the Atlantic Ocean, and in the Cayman Islands not since the 1970s. Here we report a recent record of a school of S. lewini in deep water off Grand Cayman, and describe a recent, concomitant increase in numbers of the species, and its critically endangered congener, the great hammerhead ( Sphyrna mokarran ), around the Cayman Islands. Relative population trends and seasonal patterns were assessed using data from shallow and deep-water BRUVS, scientific longlining, citizen science projects including the Sharklogger Network and REEF, and social media reports. It appears that S. lewini may be slowly re-occupying the area, selecting and using deeper waters to school, while S. mokarran has also become less scarce than hitherto.

First records of the blurred lantern shark Etmopterus bigelowi from the Cayman Islands, Western Atlantic - Austin J. Gallagher; Oliver N. Shipley; Christine De Silva; Johanna K. Kohler; Teresa F. Fernandes; Timothy Austin; Rupert F. Ormond; Mauvis A. Gore (Frontiers in Marine Science, 2023)
The genus Etmopterus is the most speciose group of small bodied deep-sea sharks found throughout the tropical and subtropical Western Atlantic. Despite exhibiting a global distribution at the genus-level, the blurred lantern shark ( Etempoterus bigelowi ) is known only from a few records in the Western and Southern Atlantic Ocean. Through in-situ video observations using deep-sea landers, we provide two new locality records of the blurred lantern shark from the deep waters off the Cayman Islands, Caribbean Sea. Three unique individuals were recorded across two separate deployments between 653m – 668m. These observations provide the first records of this species in the Caribbean Sea, adding to the minimal knowledge of the species’ distribution throughout the Western Atlantic Ocean.

Characteristics of the Isu1 C-terminus in relation to [2Fe-2S] cluster assembly and ISCU Myopathy - Brianne E. Lewis; Courtney J. Campbell; Andria Rodrigues; Lindsey Thompson; Ashutosh K. Pandey; Sarah N. Gallagher; Debkumar Pain; Andrew Dancis; Timothy L. Stemmler (JBIC Journal of Biological Inorganic Chemistry, 2022)

A Functional Interaction Between Y674-R685 Region of the SARS-CoV-2 Spike Protein and the Human α7 Nicotinic Receptor - Juan Facundo Chrestia; Ana Sofia Oliveira; Adrian J. Mulholland; Timothy Gallagher; Isabel Bermúdez; Cecilia Bouzat (Molecular Neurobiology, 2022)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Potential widespread denitrosylation of brain proteins following prolonged restraint: proposed links between stress and central nervous system disease - Timothy D. Foley; Kari S. Koval; Alexandria G. Gallagher; Stefan H. Olsen (Metabolic Brain Disease, 2019)

Distance error for determining the acoustic velocity of standing tree using tree morphological, physical and anatomical properties - Charles Essien; Brian K. Via; Thomas Gallagher; Timothy McDonald; Lori Eckhardt (Journal of the Indian Academy of Wood Science, 2018)

Sensitivity of acoustic tools to variation in equilibrium moisture content of small clear samples of loblolly pine (Pinus taeda) - Charles Essien; Brian K. Via; Thomas Gallagher; Timothy Mcdonald; Lori Eckhardt (Journal of the Indian Academy of Wood Science, 2018)

High spatial resolution burn severity mapping of the New Jersey Pine Barrens with WorldView-3 near-infrared and shortwave infrared imagery - Timothy A. Warner; Nicholas S. Skowronski; Michael R. Gallagher (International Journal of Remote Sensing, 2017)

Population pharmacokinetic and exposure-response analysis of nilotinib in patients with newly diagnosed Ph+ chronic myeloid leukemia in chronic phase - Richard A. Larson; Ophelia Q. P. Yin; Andreas Hochhaus; Giuseppe Saglio; Richard E. Clark; Hirohisa Nakamae; Neil J. Gallagher; Eren Demirhan; Timothy P. Hughes; Hagop M. Kantarjian; Philipp D. le Coutre (European Journal of Clinical Pharmacology, 2012)

Ambient UV, personal sun exposure and risk of multiple primary melanomas - Anne Kricker; Bruce K. Armstrong; Chris Goumas; Melisa Litchfield; Colin B. Begg; Amanda J. Hummer; Loraine D. Marrett; Beth Theis; Robert C. Millikan; Nancy Thomas; Hoda Anton Culver; Richard P. Gallagher; et al. (Cancer Causes & Control, 2007)

Familial aggregation of melanoma risks in a large population-based sample of melanoma cases - Colin B. Begg; Amanda Hummer; Urvi Mujumdar; Bruce K. Armstrong; Anne Kricker; Loraine D. Marrett; Robert C. Millikan; Stephen B. Gruber; Hoda Anton-Culver; Judith B. Klotz; Roberto Zanetti; Richard P. Gallagher; et al. (Cancer Causes & Control, 2004)

Familial aggregation of melanoma risks in a large population-based sample of melanoma cases - Colin B. Begg; Amanda Hummer; Urvi Mujumdar; Bruce K. Armstrong; Anne Kricker; Loraine D. Marrett; Robert C. Millikan; Stephen B. Gruber; Hoda Anton-Culver; Judith B. Klotz; Roberto Zanetti; Richard P. Gallagher; et al. (Cancer Causes & Control, 2004)

Physiological Changes in Largemouth Bass Exposed to Paper Mill Effluents Under Laboratory and Field Conditions - Maria S. Sepúlveda; Evan P. Gallagher; Timothy S. Gross (Ecotoxicology, 2004)